Association between prenatal exposure to ambient ozone, birth weight, and macrosomia in healthy women - Zheng, Chengyi; Tian, Jiaqi; Ma, Lan; Ding, Chunjie; Zhang, Lin (Frontiers in Public Health, 2022)
Studies have shown that prenatal ozone exposure is associated with increased risk of adverse pregnancy outcomes, among which abnormal birth weight is a detrimental factor for diseases in adulthood, but the association of birth weight and ozone is inconclusive. Herein, we conducted this study by enrolling 407 couples of pregnant women and collected their demographical materials, their exposure to ambient ozone was assessed according to the place of their residence. The hourly monitored ozone was first averaged to daily level, then monthly and whole-gestationally levels. After adjusting confounders, we processed multivariate generalized addictive analysis to predict the association of prenatal ozone exposure and birth weight. Besides, we divided the cohort into two categories according to whether the infant met the standard of macrosomia, and the occurrence of macrosomia was studied via univariate and multivariate logistic regression analyses as extreme conditions of the effects of ozone exposure on birth weight. We found that the ground-level ozone in Jinan changed with temperature periodically, higher in summer and lower in winter. Over the past 8 years from 2014, the ambient ozone increased by 1.74 μg/m3 per year. Of the 407 singleton-pregnant women, 21 infants were diagnosed with macrosomia. After adjusting confounders, we found that each unit increase in prenatal ozone exposure caused 8.80% (ORozone90%CI: 0.912(0.850, 0.978)) decreased risk of macrosomia, but the splined ambient ozone exposure data was not statistically associated with birth weight, which is probability due to the limited sample size. In conclusion, prenatal ozone exposure is associated with decreased risk of macrosomia but is weakly linked to birth weight.